Islamic Values in Higher Education Students’ Communication in Edmodo Learning Platform - Eros Meilina Sofa (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2018)
This present study aims to explore students’ communication styles and Islamic values performed in their communication that is mediated in Edmodo learning platform. A qualitative descriptive approach was employed in this research. This study used observation and questionnaire to collect the data and analyzed them descriptively to present a comprehensive interpretation. The findings reveal that the students integrated Islamic values through their communication styles in the online learning atmosphere. It was demonstrated through short expressions and in the content of the conversations. Not only did the values appear explicitly, but they could also be noticed implicitly in the sentences containing suggestions, polite greetings, and consoling others. Another result promotes that the use of Edmodo as a learning management system was able to enhance their active participation in the online learning. This study offers that the students could internalize Islamic values that they learned both formally and informally in their daily communication. It indicates that the use of Islamic terms and the existence of Islamic values in the English conversations made the online learning group differ considerably from other online communities